Peran dan Esensi Karang Taruna dalam Pengembangan Masyarakat di Desa Jangur - Rohman, Abdur; Islamia, Sividinal; Suciati, Eny (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat, 2024)
Karang Taruna plays a significant role in local community development, including in Desa Jangur. This research aims to explore the essence of Karang Taruna and delineate its role in community development efforts in Desa Jangur. A qualitative approach was employed in this study, examining Karang Taruna's activities, local economic empowerment programmes, skill development and educational initiatives, as well as its role in fostering solidarity and partnerships. The research findings reveal Karang Taruna's positive contributions in strengthening social networks, enhancing the community's quality of life, and facilitating the development of local potential. The implications of this research provide a foundation for enhancing Karang Taruna's role as a sustainable community development agent in Desa Jangur. This study demonstrates that Karang Taruna has a substantial role in community development in Desa Jangur. Through economic empowerment programmes, skills training, and efforts to build solidarity, Karang Taruna is able to make positive contributions to advancing the local community. By maintaining the organisation's essence and continuously engaging members actively, Karang Taruna can become a strong partner for the government and other institutions in strengthening the development of Desa Jangur. Through this research, it is anticipated that relevant parties will further recognise the important role of Karang Taruna in rural community development. It is recommended that empowerment programmes continue to be enhanced, collaboration with relevant agencies be strengthened, and Karang Taruna's role in supporting community welfare be further improved. Thus, Karang Taruna can continue to be a driving force in promoting the welfare of the Desa Jangur community and realising sustainable development.